The Role of Classroom Interaction in Online Learning: Voices From The Students - Entusiastik; Yuniar D.A. Siregar (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2022)
The importance of classroom interaction in learning has been widely researched. Through the lens of sociocultural theory, classroom interaction could be seen as mediation for learning where learners develop their knowledge and understandings through collaborative activities and dialogic processes which take place during the learning process in class. This paper qualitatively explores the types of classroom interaction that take place in an online learning environment to analyze factors that impacted and shaped classroom interactions. Further, how students perceive each type of interaction and how it might contribute to learning and learners’ satisfaction were also discussed. The study highlights the importance of balancing the use of both synchronous and asynchronous interaction modes to allow maximum classroom interaction. While technology might be a potential tool in encouraging learners to interact more actively and engage in interaction within a less threatening condition, instructors should think carefully about the design of learning activities to create positive classroom interaction with learners, among learners, and between learners and the course materials.